Virus Disinfection: Virus Disinfection from Environmental Water Sources Using Living Engineered Biofilm Materials (Adv. Sci. 14/2020). Issue 14 (22nd July 2020) - Pu, Jiahua; Liu, Yi; Zhang, Jicong; An, Bolin; Li, Yingfeng; Wang, Xinyu; Din, Kang; Qin, Chong; Li, Ke; Cui, Mengkui; Liu, Suying; Huang, Yuanyuan; et al.
Abstract : In article number 1903558, Chao Zhong and co‐workers report a simple, efficient, and environmentally friendly approach to achieve highly selective disinfection of specific viruses with living engineered biofilm materials from virus‐polluted water. The engineered biofilms can disinfect influenza virus from contaminated water to a level below the limit‐of‐detection for a qPCR‐based detection assay.